Outcomes of Total Shoulder Arthroplasty With Posterior Capsular Plication. (January 2019) - Szolomayer, Lauren K; Kuether, Justin; Kassam, Hafiz F; Mata Fink, Ana; Regnell, Elsa; Kovacevic, David; Blaine, Theodore A
Background: Glenoid loosening and instability are among the most common complications after anatomic total shoulder arthroplasty (TSA), resulting in poor function. Posterior instability is one contributing factor. The purpose of this study is to report the clinical and radiographic outcomes of a series of patients treated with posterior capsule plication for intraoperative posterior instability during TSA. It is hypothesized that patients undergoing this procedure will have improvement in posterior stability intraoperatively while not limiting their ROM postoperatively. Methods: Patients of the senior author were identified who had undergone TSA with posterior capsule plication from 2014 to 2015 based on Current Procedural Terminology (CPT) codes. Their records and preoperative radiographs were retrospectively reviewed for demographic data and preoperative range of motion (ROM) which was documented in the clinic notes. Patients were then evaluated postoperatively to determine the outcomes after TSA with posterior capsule plication. Final follow-up was conducted via telephone survey. Results: Nineteen patients were identified for review; however, only 14 had all imaging available. The mean age at the time of surgery was 63 years. There were 2 A1, 6 B1, and 6 B2 Walch-type glenoids based on preoperative imaging. All but one had equivalent or better ROM for active forward elevation and external rotation postoperatively. One patient required return to operating room at 5 months after developing adhesive capsulitis. Conclusion: This study indicates that the use of posterior capsule plication during TSA is a safe method to address posterior subluxation, while still allowing for improved ROM postoperatively.